2018
DOI: 10.3847/1538-4357/aad59a
|View full text |Cite
|
Sign up to set email alerts
|

A Multimessenger Picture of the Flaring Blazar TXS 0506+056: Implications for High-energy Neutrino Emission and Cosmic-Ray Acceleration

Abstract: Detection of the IceCube-170922A neutrino coincident with the flaring blazar TXS 0506+056, the first and only ∼3σ high-energy neutrino source association to date, offers a potential breakthrough in our understanding of highenergy cosmic particles and blazar physics. We present a comprehensive analysis of TXS 0506+056 during its flaring state, using newly collected Swift, NuSTAR, and X-shooter data with Fermi observations and numerical models to constrain the blazar's particle acceleration processes and multime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
377
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 289 publications
(418 citation statements)
references
References 87 publications
38
377
1
2
Order By: Relevance
“…Figure 4 shows the peak neutrino energy and peak ν µ + ν µ energy flux derived from equation (2). Our results are in line with predictions made for individual sources, i.e., ∼ 0.1 − 1 EeV neutrinos with fluxes much lower than in γ-rays (e.g., Dimitrakoudis et al 2014;Keivani et al 2018). There are a few blazars that are potentially interesting neutrino sources (close to IceCube's discovery potential), with LSP blazar 4FGLJ2148.6+0652 being the best example.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 4 shows the peak neutrino energy and peak ν µ + ν µ energy flux derived from equation (2). Our results are in line with predictions made for individual sources, i.e., ∼ 0.1 − 1 EeV neutrinos with fluxes much lower than in γ-rays (e.g., Dimitrakoudis et al 2014;Keivani et al 2018). There are a few blazars that are potentially interesting neutrino sources (close to IceCube's discovery potential), with LSP blazar 4FGLJ2148.6+0652 being the best example.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the derived magnetic field strengths in the emission region imply either large amplification of the jet's magnetic field or sub-pc γ-ray production sites, well within the BLR and in tension with recent results. The expected neutrino emission (for all sources in our sample) peaks at ∼ 0.1 − 10 EeV, i.e., at much higher energies than the multi-TeV neutrinos associated with TXS 0506+056 (see also Keivani et al 2018). Meanwhile, the typical peak neutrino fluxes are ∼ 10 −4 times lower than the peak γ-ray fluxes.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, only small changes in the properties of the electron energy spectrum at injection (i.e., γ e,b , s e,2 , γ e,max ) are needed to account for the spectral variability in the X-ray band. The strongest upper limits on the neutrino flux are derived for epochs where X-ray measurements (with small uncertainties) are available, in agreement with previous studies (Keivani et al 2018;Murase et al 2018). Unfortunately, during the period of the reported neutrino flare by IceCube, there are no X-ray measurements available.…”
Section: Multi-epoch Sed Modelingsupporting
confidence: 89%
“…The parameters of the best-fit power-law model (with their 1σ statistical errors) are presented in Table 3 and the 0.3-10 keV fluxes are displayed in Figure 1 (middle panel). The photon index Γ derived by the fit is consistent with the values reported by Keivani et al (2018), who analyzed individual Swift-XRT observations after the IceCube-170922A detection as part of the source monitoring program (see Figure 2 of the reference and Table 1 therein). By performing a simultaneous fit to Swift-XRT and NuSTAR data, Keivani et al (2018) found that the broadband X-ray spectrum of TXS 0506+056 is best fitted by a sum of two power-law components with best-fit photon indices of 2.37 ± 0.05 (Swift-XRT band) and 1.68 ± 0.14 for the hard part of the spectrum.…”
Section: Swift-xrtsupporting
confidence: 86%
See 1 more Smart Citation